First new species of the Phytoseius horridus group (Acari: Phytoseiidae) described from Brazil, with a key to the Brazilian species of Phytoseius - Da Silva, Guilherme Liberato; Rocha, Matheus Dos Santos; Ferla, Noeli Juarez (Zootaxa, 2013)
Phytoseius litoralis n. sp., a member of the horridus species group, is described from the State of Rio Grande do Sul, in southern Brazil, based on specimens collected on Psidium guajava, Solanum concinnum and Cecropia pachystachya. This is the first species of the horridus group described from Brazil. A key to species of Phytoseius reported from Brazil is provided.